Neurological manifestations of ehrlichiosis among a cohort of patients: prevalence and clinical symptoms - Osahon Iyamu; Emily J. Ciccone; Abigail Schulz; Julia Sung; Haley Abernathy; Aidin Alejo; Katherine Tyrlik; Victor Arahirwa; Odai Mansour; Dana Giandomenico; Monica M. Diaz; Ross M. Boyce (BMC Infectious Diseases, 2024)
Abstract Background Ehrlichiosis is a potentially fatal tick-borne disease that can progress to involve the central nervous system (CNS) (i.e., neuro-ehrlichiosis), particularly in cases where diagnosis and treatment are delayed. Despite a six-fold national increase in the incidence of ehrlichiosis over the past 20 years, recent data on the prevalence and manifestations of neuro-ehrlichiosis are lacking. Methods We conducted a retrospective chart review of all patients tested for ehrlichiosis at University of North Carolina Health facilities between 2018 and 2021 and identified patients who met epidemiological criteria for ehrlichiosis as established by the Council of State and Territorial Epidemiologists and employed by the Centers for Disease Control and Prevention. We estimated the prevalence of neurological symptoms and described the spectrum of neurological manifestations in acute ehrlichiosis, documenting select patient cases in more detail in a case series. Results Out of 55 patients with confirmed or probable ehrlichiosis, five patients (9.1%) had neurologic symptoms, which is notably lower than previous estimates. Neurological presentations were highly variable and included confusion, amnesia, seizures, focal neurological deficits mimicking ischemic vascular events, and an isolated cranial nerve palsy, though all patients had unremarkable neuroimaging at time of presentation. All but one patient had risk factors for severe ehrlichiosis (i.e., older age, immunosuppression). Conclusions Neuro-ehrlichiosis may lack unifying patterns in clinical presentation that would otherwise aid in diagnosis. Clinicians should maintain a high index of suspicion for neuro-ehrlichiosis in patients with acute febrile illness, diverse neurological symptoms, and negative neuroimaging in lone star tick endemic regions.